A haven and a hell : the ghetto in black America - Freeman, Lance (Columbia University Press, 2019)
The author traces the evolving role of predominantly Black neighborhoods in northern cities from the late nineteenth century through the early twenty-first century. This book reveals the forces that caused the ghetto's role as haven or hell to wax and wane.